2017
DOI: 10.2471/blt.17.194514
|View full text |Cite
|
Sign up to set email alerts
|

Revision of clinical case definitions: influenza-like illness and severe acute respiratory infection

Abstract: The formulation of accurate clinical case definitions is an integral part of an effective process of public health surveillance. Although such definitions should, ideally, be based on a standardized and fixed collection of defining criteria, they often require revision to reflect new knowledge of the condition involved and improvements in diagnostic testing. Optimal case definitions also need to have a balance of sensitivity and specificity that reflects their intended use. After the 2009–2010 H1N1 influenza p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
219
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(246 citation statements)
references
References 24 publications
5
219
0
4
Order By: Relevance
“…Likewise, it was not a significant predictor of confirmed influenza in all age groups in the United States study by Shah et al [12] in 2009-2011, which found that the most discriminating clinical manifestations, with an aDOR >3, were cough and fever. Our results support the removal of sore throat from the clinical case definition in order to improve performance, as suggested by other authors [5].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, it was not a significant predictor of confirmed influenza in all age groups in the United States study by Shah et al [12] in 2009-2011, which found that the most discriminating clinical manifestations, with an aDOR >3, were cough and fever. Our results support the removal of sore throat from the clinical case definition in order to improve performance, as suggested by other authors [5].…”
Section: Discussionsupporting
confidence: 92%
“…In our opinion, the impact of this limitation may be minimal, as other factors, such as individual and daily variations, the site of measurement, and the natural trend for physicians to round temperatures up or down, can influence the measured temperature [9]. Secondly, age, the influenza type and subtype [5], or the season [18] might be partially responsible for differences in the performance of the variables studied. However, we adjusted for age and season, and it seems improbable that our results are invalid.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is in keeping with surveillance definitions for influenza-like illness, which limit cough duration to 7-10 days. 37,38 Patients with respiratory viral infection were as likely as other patients to receive chest X-rays and to have abnormalities on chest X-ray. However, more than 50% of patients who had respiratory virus identified were treated with antibiotics at enrollment.…”
Section: Discussionmentioning
confidence: 99%
“… (A) Distribution of self-reported influenza-like illness cases according to the WHO definition 41 over the 10 selected urban quarters. The number of Influenza-like illness cases per incoming answers is expressed as percentage value for each quarter.…”
Section: Resultsmentioning
confidence: 99%